Strona podmiotowa czynu zabronionego a formy jego popełnienia — zagadnienia wybrane - Giezek, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The principal thesis of the study comes down to the contention that meaning of the awareness of the prohibited act perpetrator increases with movement of criminalization of behavior to the foreground of infringement of the interest protected by law and also with appearance of various forms of criminal cooperation. It is for each of the modified forms of commitment of a prohibited act — both staged as well as related to criminal cooperation — is accompanied by the increase of meaning of the elements composing the subjective side. It is not only about the state of awareness, but also about the volitional area. This tendency means that reconstruction of the subjective side in the criminal trial should focus first of all on what each of the cooperating persons wanted and what they headed to, as the extrinsic behavior can be founded on activities of other persons and in the result be subject to a far-reaching reduction. It could be even assumed that it is not the extrinsic behavior, but the state of awareness of the person cooperating in committing aprohibited act that decides about the person’s responsibility. This tendency — probably well justified from the criminal and political point of view — is also accompanied by some complications that result from the fact that it is not strictly performed to the end. Apeculiar lack of consequence is demonstrated when law makers decide for criminalization of behaviors related to unintended exposition to hazard of the interest protected by law. Aproblem also appears in case of criminal cooperation forms and it is demonstrated by lack of desired symmetry between the state of awareness and will of the cooperating persons, for there is a question if we deal with instigation in the sense of Art. 18 § 2 of criminal code, when the instigating person causes performance of the behavior, which — due to suborn person being mistaken — cannot constitute an intentional prohibited act, when in the system of law there is no its unintentional counterpart. An example of lack of the desired symmetry between the state of awareness and the will of the cooperating persons is also the situation in which we deal with participation in conceivable intent of help in committing of a crime, which can be committed by a perpetrator only with direct intent.
Keywords: awareness; subjective side; intension; forms of committing a crime; perpetration vs. subjective side; instigation vs. subjective side